Marcas à flor da pele: compreensão de professoras, pedagogas e estudantes sobre autolesões nas adolescências - Rosso, Michelle Luiza de (2025)
Self-harm is defined as a self-inflicted and intentional violent behavior, which may manifest with or without suicidal ideation. Prevalence studies indicate that adolescents are particularly vulnerable to these behaviors. Self-harm is a complex phenomenon with diverse functions for each person and different interpretative approaches from researchers and society. It is often heavily stigmatized by both family and society. In this research, we focus on understanding the perspectives of teachers, pedagogical coordinators, and adolescent students regarding self-harming behaviors during adolescence. Our general objective is to analyze how these individuals understand and respond to self-harming behaviors in adolescents, considering the age range of 10 to 19 years as the adolescent period. The research has a basic purpose, a qualitative approach, and a descriptive and exploratory nature. For data collection, 18 semi-structured interviews were conducted, involving 2 pedagogical coordinators, 4 teachers, and 12 students. The data analysis was descriptive, including one question analyzed using the Collective Subject Discourse technique, which enabled the presentation of the subjective construction of meanings attributed to self-harming behaviors by teachers, pedagogical coordinators, and students. The research was carried out in the municipality of Foz do Iguaçu, Paraná, in two public state schools, covering classes from lower secondary education (6th to 9th grade) and upper secondary education (1st to 3rd year). Among the 12 adolescent participants, 6 had a history of self-harming behaviors, while 6 did not. The results provided a detailed account of the situations experienced by the research participants in the school environment and their understanding of the various factors influencing these behaviors, highlighting the challenges schools face in handling these situations. Selfharming behaviors were associated with family conflicts, bullying, normative social pressures, discrimination, and issues related to gender and sexual identity. The data reveal a scenario marked by emotional suffering, social exclusion, and a lack of support in the school environment, emphasizing the need for specific training for school staff, strengthening support networks, and integrating education with public health services. As a research product, an educational card game was developed to encourage dialogue and reflection on self-harm and other forms of violence, aiming to deepen knowledge and present the study’s findings in a practical way to the community. The research reaffirms the urgency of transforming schools into spaces of care and building multidisciplinary networks that consider the complexity of adolescence and selfharming behaviors.